2017
DOI: 10.1103/physrevb.96.165101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoconductivity in Weyl semimetals: Effect of chemical potential and temperature

Abstract: We present detailed analyses of magnetoconductivities in a Weyl semimetal within the Born and self-consistent Born approximations. In the presence of charged impurities, linear magnetoresistance can occur when the charge carriers are mainly from the zeroth (n = 0) Landau level. Interestingly, the linear magnetoresistance is very robust against changes of temperature as long as the charge carriers come mainly from the zeroth Landau level. We denote this parameter regime as the high-field regime. On the other ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 32 publications
9
30
0
Order By: Relevance
“…This is consistent with the ∆ = 0 result in Ref. 31. In the high magnetic field limit ( B → 0) only the zeroth Landau level contributes and the equation simply yields…”
Section: A Chemical Potentialsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with the ∆ = 0 result in Ref. 31. In the high magnetic field limit ( B → 0) only the zeroth Landau level contributes and the equation simply yields…”
Section: A Chemical Potentialsupporting
confidence: 91%
“…He only studied the case with zero chemical potential and at very high magnetic fields where only the zeroth Landau level contributes to the conductivity. More recent studies [30][31][32] revisited this calculation in more detail. It was shown that the screened Coulomb impurities used by Abrikosov are crucial for reproducing the linear behavior 30 , since a completely different behavior is achieved for the simple case of short-range scatterers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The screened charged impurities are necessary to reproduce the B −1 dependence of the conductivity and thus the linear magnetoresistance, consistently with previous studies for the 2 × 2 Weyl Hamiltonian [39][40][41] . We calculated the vertex correction and showed that it is negligible for realistic parameter regimes, which justifies the assumptions in previous studies 39,40,42 . In the case of finite mass term we showed that the high field limit is qualitatively the same as in the massless case i.e.…”
Section: Summary and Discussionsupporting
confidence: 81%
“…Using this continuum model previous theoretical papers investigate the magnetoconductivity in the massless [39][40][41] and massive [42][43][44] cases. The experimentally seen linear magnetoresistance is recovered [39][40][41][42] only if screened Coulomb impurities are used. These studies use the linear response theory using the Born approximation 45 to evaluate the self-energy.…”
Section: Introductionmentioning
confidence: 99%